Micropropagation of maytenus aquifolium martius - Pereira, Ana M. S.; Moro, Jose Roberto [UNESP]; Cerdeira, Rita M. M.; França, Suzelei C. (Taylor & Francis, 1994)
Axillary buds of Maytenus aquifolium were cultured in Murashige and Skoog (MS) medium with growth regulators to induce plantlet formation. Shoot proliferation induced in MS medium supplemented 3 mg/l with 6-benzylaminopurine (BAP) was greater than in MS medium with kinetin at the same concentration. Plantlet height was also affected by both type and concentration of cytokinin. Addition of 0.2 mg/l of indole-3-acetic acid (IAA) to the medium contributed to an increase in plantlet height. Rootless plantlets were rooted successfully in vitro or ex vitro. © 1994 Taylor & Francis Group, LLC.
Keywords: Antiulcer drug; Espinheira santa; Medicinal plant; Propagation; Tissue culture